(untitled) - Faithfull, N. T. (Oxon, UK, 2002)
The book is complete with useful Internet addresses, and contains over 60 different practical methods. Each method is described by a step-by-step approach, and contains details of apparatus required, chemical reaction equations, formulae and calculations, and meticulous descriptions of experimental results. Most methods use standard equipment and instruments commonly found in the practical lab. The aim is that scientists with little experience in analytical techniques should be able to safely carry out these procedures and obtain acceptable results
Keywords: Soils,Plants,Chemistry, Analytic; Analysis,Analysis